Tobacco consumption and non-communicable diseases in Ghana; Identifying accentuating factors and further evidence from 2014 Ghana demographic and health survey - Brenyah Kwasi Joseph; Nonvignon Justice; Owusu-Dabo Ellis; Singh Arti (ELSEVIER, 2023)
This article is published by Elsevier and is also available at 10.1016/j.sciaf.2023.e01665